The Role of Social Media in the Adaptation of Russians Working in Precarious Labour Markets in Korea and China - Ryzhova, Natalya; Zhuravskaya, Tatiana (Journal of Economic Sociology, 2022)
How do migrants use social media to adapt to new social conditions, including those in the labour market? Does it matter which social media and how many of them are available for migrants? Answering these questions, we focus on particular social groups—Russian citizens engaged in precarious work in China and South Korea. These labour market segments have hardly been described in the academic literature, mainly because such migrant flows are not observable in the receiving or sending country. As a rule, these people do not have legal migration status (they do not have work permits, long-term residence permits, insurance, and other necessary documents). We aim to compare two situations—the Korean one, where different social media (WhatsApp, VK, Viber, and others) are available to migrants, and the Chinese one, where WeChat dominates, and hence, in so doing to understand what happens in the context of one dominant media. In addition to analyzing work requests and job vacancies published in social media (WeChat, VK, Telegram, WhatsApp), we use in-depth interviews with precarious workers (23 interviews obtained in China and 31 in Korea).